Determination of mechanical properties and environmental impact due to inclusion of flyash and marble waste powder in concrete. (June 2020) - Varadharajan, S.
Abstract: The production of marble waste powder (MWP) and flyash is one of the significant source of pollution in developing countries. Both MWP and flyash are generated in enormous quantities, and their disposal poses a big problem. Due to their binding properties, both flyash and MWP can be effectively used in concrete to enhance its properties. In this study, MWP is used to replace fine aggregate up to 30%, and PPC, consisting of approximately 30% flyash, is used to manufacture eco-friendly concrete. Also, hooked steel fibres are added from 1% to 3% to enhance the mechanical properties of concrete. The results of the experimental study indicate an enormous increase in mechanical properties in comparison to previous research works. The environmental impact assessment is performed using recipe midpoint and endpoint analysis, which shows a positive impact due to the inclusion of flyash and marble waste powder in concrete. The economic feasibility study indicates a cognitive enhancement of cost, which is justified in return for an excellent improvement in mechanical and permeability properties along with a positive impact on the environment leading to sustainable development.